Paciente femenino de 19 años con neumonía nosocomial. - Santamaría Meléndez, Cindy Claribel (2020)
Intra-hospital or nosocomial pneumonia is considered the second most common infection with hospital origin, with an occurrence of 4 to 7 cases out of every 1,000 hospital discharges. Based on their dominant morbidity and mortality, the pathogenic peculiarities since the causal microorganisms are unequal to those that produce community-acquired pneumonia, nosocomial pneumonia and pneumonia associated with mechanical ventilation make up an internal subgroup of infections of the apparatus respiratory. Research on this topic is extremely important since Nosocomial Pneumonia is considered one of the 10 most frequent causes of death in hospitalized patients and due to this it is necessary to enunciate the elements and influential contexts in the contagion of nosocomial pneumonia, as well as its risk factors for adolescent patients and the necessary prevention in order to avoid many cases. The purpose of this work is to determine the elements and contexts influencing the contagion of nosocomial pneumonia in the 19-year-old patient. It was possible to corroborate that by means of a union of criteria for the diagnosis and a correct process of medication and respiratory physiotherapy technique, the health of the patient could be improved, a change in eating habits was recommended, leaving aside the diet that the patient made without the respective approval of a professional in nutrition. It should be noted that there are no measures to completely eradicate these respiratory infections, but there are a series of resources that will help us to identify it and a series of preventions with which the risk of contracting them can be reduced.